2023
DOI: 10.3390/dairy4030033
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Supplementation in Small Ruminants: A Review on Their Possible Role in Rumen Fermentation, Microbiota, and Animal Production

Mariangela Caroprese,
Maria Giovanna Ciliberti,
Rosaria Marino
et al.

Abstract: Essential oils are bioactive compounds, originating from the secondary metabolism of plants, recognized for their ability to modify rumen fermentation, gut health, and to function as antioxidant molecules in small ruminants. Indeed, small ruminant-derived products, such as milk, dairy, and meat can benefit from the utilization of essential oils, that have demonstrated antimicrobial, antioxidant and anti-inflammatory affects, in the animals’ diet. This review reports on the findings that demonstrates the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Some essential oils can influence rumen fermentations and reduce CH 4 production in vitro. Encouragingly, certain studies have demonstrated remarkable reductions in CH 4 emissions of up to 90% [ 64 ]. However, with the increased use of EOs, there is a need for regulations that include maximum permissible limits, toxicity considerations, and the capacity of EOs against specific methanogens, ensuring that they do not adversely affect other groups of microorganisms in the rumen.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…Some essential oils can influence rumen fermentations and reduce CH 4 production in vitro. Encouragingly, certain studies have demonstrated remarkable reductions in CH 4 emissions of up to 90% [ 64 ]. However, with the increased use of EOs, there is a need for regulations that include maximum permissible limits, toxicity considerations, and the capacity of EOs against specific methanogens, ensuring that they do not adversely affect other groups of microorganisms in the rumen.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…Following China's 2020 ban on antibiotic utilization, there has been an increase in research on alternative feed additives, such as Chinese herbal additives, micro-ecological preparations, and plant essential oil extracts (Meena et al, 2022 ; Yang et al, 2022 ; Caroprese et al, 2023 ; Guo et al, 2023 ; Kiernan et al, 2023 ; Ramdani et al, 2023 ; Varga-Visi et al, 2023 ). While most research has focused on swine and poultry, applications in sheep are less common.…”
Section: Introductionmentioning
confidence: 99%
“…Following China's 2020 ban on antibiotic utilization, there has been an increase in research on alternative feed additives, such as Chinese herbal additives, micro-ecological preparations, and plant Abbreviations: DPF, defective pear fermentation; ADG, average daily gain; ADFI, average daily feed intake; SOD, superoxide dismutase; MDA, malondialdehyde; GSH-Px, glutathione peroxidase; GLU, glucose; TG, triglycerides; TC, total cholesterol; HDL-C, high density liptein cholesterol; LDL-C, low density liptein cholesterol; PL, papillae length; PW, papillae width; MT, muscular thickness; VH, villus height; CD, crypt depth; V/C, villus height/crypt depth. essential oil extracts (Meena et al, 2022;Yang et al, 2022;Caroprese et al, 2023;Guo et al, 2023;Kiernan et al, 2023;Ramdani et al, 2023;Varga-Visi et al, 2023). While most research has focused on swine and poultry, applications in sheep are less common.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent evidence has demonstrated that EOs might modulate the immune system, antioxidant activity, and udder health of dairy animals [7]. Moreover, EOs have been found to improve rumen fermentation efficiency by altering gut microbiota and sustaining the integrity of the intestinal barrier, gut immune responses, and growth performance, supporting small-ruminant-derived products [8].…”
Section: Introductionmentioning
confidence: 99%